2008
DOI: 10.1007/s00344-008-9060-9
|View full text |Cite
|
Sign up to set email alerts
|

The Method of ABA Application Affects Salt Stress Responses in Resistant and Sensitive Potato Lines

Abstract: The phytohormone abscisic acid (ABA) has been proposed to act as a mediator in plant responses to a range of stresses, including salt stress. Most studies of ABA response apply ABA as a single dose. This may not resemble the prolonged increasing endogenous ABA levels that can occur in association with slowly increasing salinity stresses in nature or field situations. Salt stress response based on method of ABA application was examined in four potato genotypes of varying salt stress resistance: the sensitive AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…ABA induced adaptation to salt stress in suspension cultures of tobacco (Nicotiana tabacum L. Cv. Wisconsin) has been also reported by Etehadnia et al (2008).…”
Section: Introductionmentioning
confidence: 62%
“…ABA induced adaptation to salt stress in suspension cultures of tobacco (Nicotiana tabacum L. Cv. Wisconsin) has been also reported by Etehadnia et al (2008).…”
Section: Introductionmentioning
confidence: 62%
“…Grafting to either salt‐tolerant scions or rootstocks with inherently high ABA levels may positively modify the subsequent responses of plants under salt stress by increasing plant water contents and the accumulation of dry and fresh matter (Etehadnia et al . ). Here, we found that the low thermotolerance of Cs/Cs plants was associated with the lack of ABA biosynthesis in both roots and leaves when exposed to aerial heat stress (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…For example, tetraploid Rangpur lime rootstock increases drought tolerance via the enhancement of constitutive root ABA production (Allario et al 2013). Grafting to either salt-tolerant scions or rootstocks with inherently high ABA levels may positively modify the subsequent responses of plants under salt stress by increasing plant water contents and the accumulation of dry and fresh matter (Etehadnia et al 2008).…”
Section: Aba Is Involved In Rootstock-induced Hsp70 Accumulation and mentioning
confidence: 99%
“…Cram and Pitman () showed for maize and barley that the transport of K + and Cl − from the cut ends of roots could be inhibited when roots were placed in an ABA solution. The effect of ABA applied to roots on the response of potatoes to salt stress was dependent on the method of ABA application via a single dose or by slowly increasing multiple doses (Etehadnia et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Little research has been undertaken on grapevines to investigate the role of exogenous ABA application on uptake of ions by roots, with the majority of reports dealing with the effect of foliar‐applied ABA on fruit ripening (Koyama et al , Gu et al , Balint and Reynolds ). Application of ABA to the roots in the present study was based on the general view from the literature that this would be more likely to impact on root‐to‐shoot ion transport (Etehadnia et al ). Also many soil stresses including salinity stimulate ABA synthesis in the roots of plants [reviewed in Davies et al ()], and ABA can be taken up readily from the soil solution (Hartung et al ).…”
Section: Introductionmentioning
confidence: 99%